2007
DOI: 10.1111/j.1600-0420.2007.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of intraocular lens power: a review

Abstract: This review describes the principles and practices involved in the calculation of intraocular lens (IOL) power. The theories behind formulas for calculating IOL power are described, using regression and optical methods employing 'thin lens' and 'thick lens' models, as well as exact ray-tracing methods. Numerical examples are included to illustrate the points made. The paper emphasizes the importance of establishing an accurate estimation of corneal power as well as an accurate technique for the measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
232
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(248 citation statements)
references
References 61 publications
2
232
0
14
Order By: Relevance
“…The error in measurements of the keratometric data can lead to unwanted postoperative refractive error. Although keratometric mistakes are not the first or most frequent source of error in today's biometric methods, 1 keratometry has an undisputed and important role in cataract surgery. Moreover, cases of implantation of toric IOLs require more precise keratometric readings and cylinder axis determination than ever before.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…The error in measurements of the keratometric data can lead to unwanted postoperative refractive error. Although keratometric mistakes are not the first or most frequent source of error in today's biometric methods, 1 keratometry has an undisputed and important role in cataract surgery. Moreover, cases of implantation of toric IOLs require more precise keratometric readings and cylinder axis determination than ever before.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Our sample had a mean age (± SD) of 70.2 (± 10.7) years, over double that of Ho et al's sample at 34.4 (± 16.1) years; 6 given that ELP is positively correlated with age (ELP increases with age) 4 , this may account for the slight tendency towards overestimation with the SRK/T keratometry-independent ELP estimation method in our study, when compared with that of Ho et al 6 However, this relationship between ELP and age fails to explain the observed discrepancy between the slight underestimation seen when using the Holladay 1 keratometryindependent ELP estimation method in our study, when compared with that of Ho et al 6 While our sample was less myopic, with a mean spherical equivalent of -0.89 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 further in the differing axial lengths of the two studies [mean ± SD: current study:…”
Section: -24mentioning
confidence: 94%
“…The vergence equation was used to calculate the anterior corneal plane value of the posterior corneal astigmatism as follows [ 16 ]:…”
Section: Aq1mentioning
confidence: 99%
“…Total corneal power was calculated using a thick lens formula based on corneal thickness, anterior corneal radius, and posterior corneal radius [ 16 ].…”
Section: Aq1mentioning
confidence: 99%